A comparative study of root canal preparation using flexmaster rotary and NiTi hand files - Tabrizizadeh M; Nekoofar N (Tehran University of Medical Sciences, 2006)
Background and Aim: Maintaining the original canal path and safety of canal preparation during instrumentation in curved canals have been subjected to many challenges. The aim of this study was to compare several parameters of root canal preparation using flexmaster rotary and hand used Nickel-Titanium instruments. Materials and Methods: In this experimental study, sixty extracted human teeth with root canal curvatures between 10 and 42 degress were devided into two similar groups with equal mean curvatures. Root canals in one group were prepared using flexmaster rotary instruments and the other with NiTi hand files.After canal preparation, different parameters such as straightening of curved root canal, loss of working length, fracture rate, perforation and working time, were evaluated and compared between the two groups. Data were analyzed by t student test with p<0.05 as the limit of significance. Results: Results showed that both instruments maintained the original canals' curvature. No loss of working length, instruments fracture or perforation was recorded. Working time was significantly shorter for flexmaster than hand files. Conclusion: Both systems under investigation respected original root canal curvature and were safe to use. Therefore the rotary techniques could be successfully introduced to undergraduate endodontic programmes.